2020
DOI: 10.1021/acs.estlett.0c00615
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Ambient Sulfur Trioxide (SO3) Detection: Possible Formation Mechanism and Atmospheric Implications

Abstract: Sulfur trioxide (SO 3 ) is a crucial compound for atmospheric sulfuric acid (H 2 SO 4 ) formation, acid rain formation, and other atmospheric physicochemical processes. During the daytime, SO 3 is mainly produced from the photo-oxidation of SO 2 by OH radicals. However, the sources of SO 3 during the early morning and night, when OH radicals are scarce, are not fully understood. We report results from two field measurements in urban Beijing during winter and summer 2019, using a nitrate-CI-APi-LTOF (chemical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 62 publications
4
27
0
Order By: Relevance
“…The abundance of HCl and HBr in the polluted urban troposphere may further influence the photochemistry of the atmosphere through the following two aspects: (1) direct contributions to the production of highly reactive halogen atom (e.g., Cl q and Br q ), which can rapidly oxidize VOCs (Reaction R5); and (2) replenishment of the halide ion (Cl − and Br − ) in the aerosols, supporting the nocturnal heterogeneous production of ClNO 2 and BrNO 2 , which are major sources of highly reactive halogen atom at sunrise (Reactions R3 and R4). Our observation of elevated HCl and HBr may indicate an important recycling pathway of Cl and Br species and may provide a plausible explanation for the recent observations of widespread halogen activation in polluted areas of China (e.g., Tham et al, 2016;Zhou et al, 2018;Xia et al, 2020;, which could have a significant influence on the atmospheric oxidation capacity and secondary aerosol formation. The atomic Cl and Br on polluted days might contribute to oxidation capacity to a greater extent than on clean days.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The abundance of HCl and HBr in the polluted urban troposphere may further influence the photochemistry of the atmosphere through the following two aspects: (1) direct contributions to the production of highly reactive halogen atom (e.g., Cl q and Br q ), which can rapidly oxidize VOCs (Reaction R5); and (2) replenishment of the halide ion (Cl − and Br − ) in the aerosols, supporting the nocturnal heterogeneous production of ClNO 2 and BrNO 2 , which are major sources of highly reactive halogen atom at sunrise (Reactions R3 and R4). Our observation of elevated HCl and HBr may indicate an important recycling pathway of Cl and Br species and may provide a plausible explanation for the recent observations of widespread halogen activation in polluted areas of China (e.g., Tham et al, 2016;Zhou et al, 2018;Xia et al, 2020;, which could have a significant influence on the atmospheric oxidation capacity and secondary aerosol formation. The atomic Cl and Br on polluted days might contribute to oxidation capacity to a greater extent than on clean days.…”
Section: Discussionsupporting
confidence: 56%
“…A significant source of atomic chlorine from the heterogeneous reaction of N 2 O 5 onto chloride aerosol (Reaction R3) was observed in Boulder, United States, which is 1400 km from the nearest coastline, indicating that active chlorine chemistry also occurs in regions far from the ocean (Thornton et al, 2010). Follow-up studies have confirmed the presence of halogen activation spreading over the continental regions of North America, Canada, Europe and Asia (Mielke et al, 2011;Phillips et al, 2012;Riedel et al, 2013;Tham et al, 2016;Tham et al, 2018;Liu et al, 2017;Xia et al, 2020;Zhou et al, 2018;McNamara et al, 2020). These findings suggest the crucial role of HCl gas-particle partitioning in sustaining the aerosol chloride concentrations in continental regions for Reaction (R3) to take place (Brown and Stutz, 2012).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The much lower J7 observed at MT station is very likely associated with the low H2SO4 concentration at this station, which we will discuss in section 3.2.4. ruled out either. Also, the J7 at UB station could be affected by particle emissions due to the proximity of the location to the highway (Kontkanen et al, 2020).…”
Section: Particle Formation and Growth Rates At Both Stationsmentioning
confidence: 99%
“…organics-NH 3 nucleation (Lehtipalo et al, 2018), and SA-H 2 O-NH 3 -amine nucleation (Myllys et al, 2019;Yu et al, 2012). Both the nucleation rate (J nuc ) and the initial growth rate of newly formed particles tend to have a power-law relationship with the SA concentration: J nuc = k × SA α , where the activation nucleation is dominant when α ≈ 1 (Kulmala et al, 2006), the kinetic nucleation is dominant when α ≈ 2 (Riipinen et al, 2007;Paasonen et al, 2009;Erupe et al, 2010) and the thermodynamic nucleation becomes more crucial when α is larger than 2.5 (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%